Systematic studies of Australian stipoid grasses (Austrostipa) based on micro-morphological and molecular characteristics - BETTY MAULIYA BUSTAM (Society for Indonesian Biodiversity, 2010)
Bustam BM (2010) Systematic studies of Australian stipoid grasses (Austrostipa) based on micro morphological and molecular characteristics. Biodiversitas 11: 9-14. This research is one of many studies on stipoid grasses organized by the International Stipeae Working Group (ISWG). This research tested the subgeneric classification of Austrostipa proposed by Jacobs and Everett (1996) and tested how informative the micro morphological characters used. Data were collected from herbarium specimens of 36 species (33 species of Austrostipa, two species of Hesperostipa and one species of Anemanthele) at Royal Botanic Gardens, Sydney. Twenty eight micro morphological characters were used. The data were collected from both adaxial and abaxial surfaces of leaves, and from the lemma epidermis using a scanning electron microscope (SEM). ISWG provided the molecular data. Parsimony analysis and a distance method (Unweighteic Pair Group with Arithmatic Mean: UPGMA) were used to analyze micro-morphological and molecular data separately. Only UPGMA analysis was used to analyze the combined data. The results support the monophyly of Austrostipa. However, there is a little support for the subgeneric classification of Austrostipa proposed by Jacobs and Everett (1996), other than for the consistent recognition of Falcatae. The characters for comparisons between genera are too homoplasious at this level and do not contain enough information for analyses at subgeneric level, a problem apparently shared with the DNA sequences.Key words: Austrostipa, stipoid grasses, micro morphological, molecular